Effect of Drip Irrigation and Mulch on Soil and Perfohmance of Date Palm Under Saline Water Irrigatio - Jain, B L; Pareek, O P (Annals of Arid Zone, 2016)
Date palm cv 'Khadrawy' and 'Shamran' were irrigated with waters of EC 2.7, 6.0 and 9.0 dSm-1• Salt accumulations in soil, considerably higher during irrigation phase in pre-monsoon period, were effectively leached by the seasonal rainfall in conjunction with runoff from microcatchment during monsoon period. No carryover of salts was evident during five years of study. Drip irrigation was effective in limiting the salt accumulation. Gravel mulch did not show any ameliorative effect in saline water irrigation.